An Empirical Analysis of Islamic Banking (IBs) Contribution to Indonesia’s Inclusive Growth - Ibrahim, Muhammad Yusuf; Indra, Indra (Universitas Muhammadiyah Yogyakarta, 2021)
The research is aim to attest and assess empirically the contribution of Islamic banking (IBs) on the inclusive growth in Indonesia. By taking a trial-stage method i.e. descriptive analysis to elaborate a statistical data, autoregressive distributed lag (ARDL) model to assess empirically the contribution in a long-term, and error correction model (ECM) to assess the contribution in a short-term empirically. The findings are, total deposits and total financing only contribute positively significant into GDP and gini ratio in a long-term, that similiar with the previous study. Then, a total financing contribute negatively to all indicators of inclusive growth in a long-term, but, its only significance on GDP and gini ratio. But, it was contribute significantly to all indicators in a short-term. So. The findings was only evidence the significance contribution of IBs on inclusive growth in a short-term. Based on it, a long-term contribution of IBs still cathegorized as the area that requires an extentions in order to accomplish it. Â